Material Selection of Below-knee Leg Prosthetics - Rizqillah, Raihan Kenji (Journal of Materials Exploration and Findings, 2022)
The effort to select the best pylon material, part of below-knee leg prosthetic, has been performed. It begins with function analysis to generate design requirement, which concludes that the objective is to select material that gives proper mechanical properties with lowest weigth and cost. Constraint requirements eliminate unsuitable material. Material indices, a scoring function, are derived from objective with respect to a function, and used for ranking material candidates. Ranking from material indices gives top material candidates of woods. Al alloy, Mg alloy, and ferrous alloy. Further seek of documentation is undertaken by failure analysis, value analysis, fabrication, and environmental impact. The final decision is PLA carbon fibre is the best material for pylon of below knee in respect to performance to weigth and cost.